Gender- and age-specific trends in coronary heart disease mortality in France from 2000 to 2007: results from the MONICA registers. (January 2014) - Wagner, Aline; Arveiler, Dominique; Ruidavets, Jean Bernard; Bingham, Annie; Montaye, Michèle; Ferrières, Jean; Dallongeville, Jean; Haas, Bernadette; Ducimetière, Pierre
Background: Several recent studies in the USA, the UK and Australia have raised concern about a possible plateau or even reverse trend in coronary heart disease (CHD) mortality in younger populations. We aimed to assess the recent gender- and age-specific trends in CHD mortality among inhabitants aged 35–74 years from the three geographical areas covered by the French MONICA population registers. Methods: Registered events were fatal myocardial infarctions and coronary deaths selected after a thorough investigation by the physician who signed the death certificate, general practitioners and cardiologists, and by public and private hospitals for in-hospital deaths. Results: From 2000 to 2007 age-standardized CHD mortality rates decreased significantly by 24% in men and 38% in women. In the age group 55–74, the estimated annual percentage change (EAPC) in mortality was −5.2 (95% confidence interval: −6.6 to −3.7; p  < 10 −4 ) among men and −9.0 (−11.6 to −6.4; p  < 10 −4 ) among women. In the 35–54 age group, the EAPC in mortality was −4.1 (−7.2 to −1.1; p  < 10 −2 ) among men and −2.5 (−8.7 to 3.7; p  = 0.43) among women. These trends remained similar when possible coronary deaths were also accounted for, except in young men where the decline was no longer significant. Conclusions: A clear decline in recent CHD mortality rates was observed among subjects above 54 years, but not among younger subjects, particularly in women. These results may be due to unfavourable trends in some risk factors in the latter age group and call for a strengthening of primary prevention.